AB0392 ASSOCIATION BETWEEN FCGRIIA R131H, FCGRIIIA NA1/NA2 AND FCGRIIIB V158F POLYMORPHISM AND RESPONSIVENESS TO BIOLOGICS IN RHEUMATOID ARTHRITIS TUNISIAN PATIENTS. (June 2019) - Moalla, Myriam; Mahmoud, Ines; Sfar, Imen; Tekaya, Aicha Ben; Saidane, Olfa; Tekaya, Rawdha; Aouini, Saloua; Abdelghani, Kawther Ben; Laatar, Ahmed; Gorgi, Yousr; Abdelmoula, Leila
Abstract : Background: Even though biologics have been used for several years in treatment of rheumatoid arthritis (RA), little is known about factors that modify their pharmacokinetics and therefore their efficacy. Polymorphisms (SNPs) in receptors for constant region Fc of IgG (FcgR) might influence the therapeutic outcome of molecules that incorporate an Fc fragment in their structure such as etanercept (ETA), adalimumab (ADL) infliximab (IFX) and rituximab (RTX). Objectives: The aim of our study was to determine whether the presence of low affinity allele of FcgR (FcgRIIA-131R, FcgRIIIA-158F and FcgRIIIB-NA2) influences efficiency and immunogenicity of ETA, ADL, IFX and RTX in RA Tunisian patients. Methods: We included RA patients treated with biologics for at least six months. Response to treatment was assessed according to EULAR criteria. Quantitative measurement of antidrug antibodies (ADAb) for each biologic agent was carried out by a commercial enzyme-linked immunosorbent assay (ELISA) kit (Promonitor®). To do so, blood samples were collected for each patient right before drug administration. FcgRIIA, FcgRIIIA and FcgRIIIB SNPs was genotyped for all patients using PCR-SSP and direct sequencing process. Results: Seventy-nine RA patients treated with biologics were enrolled (18 with ETA, 13 with ADL, 16 with IFX and 32 with RTX). Regardless of biologic type, 61 patients (77.2%) responded to treatment and 14 patients (17.7%) developed ADAb. Genotypic study revealed a correlation between poor response to treatment and the presence of at least one FcgRIIA 131-R allele (94.7% for RH/RR genotypes versus 5.3% for H/H genotype). But, the difference was not statistically significant (p=0.25). Besides, this mutant allele was significantly associated to the presence of ADAb (71.4% of ADAb positivity for RH/RR genotypes versus 28.6% for H/H genotype: p=0.041). The haplotypic study shows that the risk allele combination of FcgR IIA-131R/IIIA-158F/IIIB-NA2 was more frequent in ADAb+ (27%) compared to ADAb- subjects (23%) and in non-responders (27%) versus good responders (23%). But, neither of these associations was statically significant. Conclusion: Our study suggests that RA patients FcgRIIA-131R allele carriers are more susceptible to develop ADAb than those with HH wild genotype. That could be explained by a higher biologic clearance in H-carrier patients, resulting in a decreased half-life and ultimately a lower risk of ADAb formation. Thus, FcgR polymorphism genotyping may be a useful marker for predicting response to Fc-containing biologics in Tunisian RA patients. Further studies need to be done on larger population. References: [1] Romero-Cara P, Torres-Moreno D, Pedregosa J, Vílchez JA, García-Simón MS, Ruiz-Merino G, Morán-Sanchez S, Conesa-Zamora P. A FCGR3A Polymorphism Predicts Anti-drug Antibodies in Chronic Inflammatory Bowel Disease Patients Treated With Anti-TNF. Int J Med Sci2018; 15(1):10-15 [2] Lee YH, Bae SC. Associations between PTPRC rs10919563 A/G and FCGR2A R131H polymorphisms and responsiveness to TNF blockers in rheumatoid arthritis: a meta-analysis. Rheumatol Int. 2016Jun;36(6):837-44. [3] Lee YH, Bae SC, Song GG, Functional FCGR3A 158 V/F and IL-6 -174 C/G polymorphisms predict response to biologic therapy in patients with rheumatoid arthritis: a meta-analysis. Rheumatol Int. 2014Oct;34(10):1409-15. Disclosure of Interests: None declared